The impact of climate risk on the soundness of local commercial banks in China—based on physical risk and transition risk - Xu, Yang; Wang, Yiqiu; Xie, Meng; Guo, Chong (Frontiers in Physics, 2025)
Climate risk has a negative impact on the stable operation of social, economic, and financial systems. Local commercial banks operate in a single geographical area and are unable to effectively diversify risk. This article uses data from local commercial banks from 2009 to 2021 to explore the impact of climate risk on the soundness of local commercial banks. The research results show that climate risk, represented by extreme rainfall and transition risk, affects the soundness of local commercial banks by increasing direct losses to credit entities, reducing corporate profitability, and decreasing corporate credit demand. Further analysis shows that for rural commercial banks, extreme rainfall and extreme high temperatures diminish their soundness by affecting agricultural production. In regions with high temperatures, extreme heat reduces workers’ labor income and the productivity of enterprises’ labor, thereby affecting the soundness of local commercial banks. The larger the scale, the higher the degree of digital transformation, and the higher the level of property insurance of local commercial banks, the smaller the impact of climate risk on their soundness. Therefore, it is suggested that local commercial banks should raise awareness of climate risk, expand their business scope, increase insurance coverage for credit entities, and accelerate digital transformation to maintain stable operations in the context of increasing climate risk.